Peran Orang Tua Upaya Peningkatan Pembelajaran Anak Usia Dini Dengan Media Digital Interaktif - Eben Ezer; Rismayanti Rismayanti; Nafa Riyona (Universitas Bina Sarana Informatika, 2021)
Interactive digital media is a computer-based learning media that contains images, narration, music, games and animations that can train the visual and auditory development of PAUD students with interactive designs so that they are able to train children's motor skills. Early childhood is a child aged 0-6 years or also called the golden egg or golden child, and is a very important age to receive maximum learning so that this period affects the future of the child. So, parents must be active in supervising their child's learning wisely and purposefully. Interactive digital media can provide variety and innovation in children's learning and as a refresher in the process, it can also make children happier without any element of coercion.